2022
DOI: 10.1002/jcp.30877
|View full text |Cite
|
Sign up to set email alerts
|

Differential recruitment of monocyte‐derived macrophages in control and stellate cell‐depleted mice during recurrent carbon tetrachloride‐induced acute liver injury

Abstract: Liver depleted of hepatic stellate cells (HSCs) is resistant to ischemia/reperfusion-, concanavalin A-, and acetaminophen-induced acute injury. Whether HSCs regulate carbon tetrachloride (CCl 4 )-induced acute liver injury is not known. CCl 4 treatment damages pericentral hepatocytes that express CCl 4 -metabolizing Cyp2E1 and activates HSCs. We investigated whether HSC-depletion in mice transgenic for thymidine kinase under the glial fibrillary acidic protein promoter (GFAP-TK-Tg) confers resistance to injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As recent studies have shown that macrophages characterized by high F4/80 and Ly6C expression, which are activated in response to hepatocyte necrosis and inflammation, produce inflammatory cytokines such as TNF-α and IL-1β 33 , 34 , which exacerbates inflammation. In this study, the proportions of F4/80 + and Ly6C + macrophages in the liver were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As recent studies have shown that macrophages characterized by high F4/80 and Ly6C expression, which are activated in response to hepatocyte necrosis and inflammation, produce inflammatory cytokines such as TNF-α and IL-1β 33 , 34 , which exacerbates inflammation. In this study, the proportions of F4/80 + and Ly6C + macrophages in the liver were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Once activated, macrophages secrete factors that exacerbate inflammation. Specifically, in the liver, F4/80 + Ly6C + macrophages are known to produce inflammatory cytokines such as TNF-α and IL-1β 33 , 34 . These cytokines activate HSCs, leading to collagen fiber production, which is foundational to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since expression of cytoglobin, which regulates CYP2E1‐induced APAP metabolism in hepatocytes and is expressed primarily by HSCs (Teranishi et al, 2015), is reduced in HSC‐depleted mice, it is plausible that the metabolism of APAP to toxic metabolites is inhibited in vivo in HSC‐depleted mice. However, when HSC‐depleted mice were challenged with CCl4, which is also metabolized by CYP2E1 to the toxic trichloromethyl (CCl3˙) and trichloromethyl peroxyl (CCl3COO˙) radicals, hepatic injury was similar to that in HSC‐sufficient mice (Sharma et al, 2022). This suggests that despite lower activity of CYP2E1 in vivo due to cytoglobin deficiency, the liver cells in HSC‐depleted mice are able to metabolize CCl4 with similar efficiency as HSC‐sufficient mice.…”
Section: Hsc‐depletion Mouse Modelmentioning
confidence: 99%